Correlation of prostate volume with ’International Prostate Symptom Score’ and ’Benign Prostatic Hyperplasia-Impact Index’ in benign prostatic hyperplasia - Gnyawali, D; Sharma, U (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Benign prostatic Hyperplasia is a common disorder and cause of morbidity in the ageing men. The evaluation symptoms and the bother associated with it are important for management. International Prostate Symptom Score (IPSS), Quality of life (QOL) and Benign Prostatic Hyperplasia Impact Index (BII) are practiced to quantify the severity of the disease. The size of prostate gland does not correlate with lower urinary tract symptoms. Correlation among above scoring is also not clear. Aim of the study is to evaluate correlation of prostate volume with International Prostate Symptom Score, Benign Prostatic Hyperplasia Impact Index and prostate size. Methods: Prospective study. Ninety-eight patients were included. Patients were assessed preoperatively with the International Prostate Symptom Score, Benign Prostatic Hyperplasia Impact Index and prostate volumes by trans abdominal ultrasound. Results: The mean age was 66.7 ± 7.3 years (50- 84) the mean IPSS, QOL, BII and prostate volumes were 23.6 ±6.0, 5.1 ± 0.9, 7.1±2.4 and 47.5±16.63 respectively. There was positive correlation between the IPSS and BII, IPSS and QOL and BII and QOL (rs= 0.89, 0.585 and 0.530 respectively) and no correlation between IPSS and BII with prostatic weight. (rs= -0.04 and -0.07 respectively). Conclusion: Management of the benign prostate hyperplasia should be considered on the bother symptoms and not on the size of the prostate. Journal of Society of Surgeons of Nepal Vol.17(1) 2014: 6-10